A cross-sectional study of patients presenting to an urban emergency department in Mwanza, Tanzania - Kotecha, Shahzmah Suleman (Division of Emergency Medicine, 2025)
Introduction: Tanzania suffers from limited healthcare resources, accentuated by the burden of trauma and infectious diseases. There is limited data on the profile of patients attending Emergency Departments (ED). This study describes patients attending the Bugando Medical Centre, Mwanza, Tanzania ED. Methods: A cross-sectional descriptive study was conducted including all patients presenting from 01 – 31 January 2023. Information collected included demographics, referral status, main complaint, ED disposition, hospital length of stay for admitted patients, and hospital outcomes for admitted patients. Results: A total of 3390 patients presented, and 3224 (98%) were included, of which 49.1 % were male, and the median age was 30 years (interquartile range 12-51). Most (72.9%) were self-referrals. The nature of the complaint for the majority of the patients (61.6%) was medical, and the overall median hospital length of stay was 5 days (IQR of 3-12 days) for admitted patients. Higher proportions (17.3% and 18.9%) of patients presented on Mondays and Tuesdays respectively. Among patients aged 14 years and above, hypertensive heart disease with failure, malignant neoplasm of the oesophagus and intracranial injury were the top medical, surgical and trauma diagnoses respectively. In the paediatric population (<14 years), sickle cell anaemia in crisis, hydrocephalus and diffuse traumatic brain injury were the top medical, surgical and trauma diagnoses respectively. The most common complaints among the patients presenting to the ED were gastrointestinal complaints (8.9%), respiratory complaints (3.1%) and congenital abnormalities (3.2%) in the >14 years, 1-14 years and <1 year age groups respectively. Most (63.6%) patients were discharged directly from the ED, and ED and in-hospital mortality were 0.2% and 15.5% respectively. Conclusion: In this study, we observed a high burden of medical complaints, a high rate of ED discharge and high in-hospital mortality. This study can inform future studies in resource mobilization and allocation for the ED, and the health system.